2010
DOI: 10.1093/eurheartj/ehq246
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency is associated with sudden cardiac death, combined cardiovascular events, and mortality in haemodialysis patients

Abstract: AimsDialysis patients experience an excess mortality, predominantly of sudden cardiac death (SCD). Accumulating evidence suggests a role of vitamin D for myocardial and overall health. This study investigated the impact of vitamin D status on cardiovascular outcomes and fatal infections in haemodialysis patients.Methods and results25-hydroxyvitamin D [25(OH)D] was measured in 1108 diabetic haemodialysis patients who participated in the German Diabetes and Dialysis Study and were followed up for a median of 4 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
183
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(199 citation statements)
references
References 44 publications
10
183
0
6
Order By: Relevance
“…In line with these experimental evidences, considerable epidemiologic data showed an important link between vitamin D deficiency and adverse cardiovascular outcomes in both the general population 14,24,25 and patients with CKD. 15,26,27 Some retrospective and observational analyses as well as shortterm uncontrolled data suggested potential survival or cardiovascular benefit of 1,25(OH) 2 D 3 treatment in patients with CKD. [17][18][19]28,29 However, controlled data remain scarce.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these experimental evidences, considerable epidemiologic data showed an important link between vitamin D deficiency and adverse cardiovascular outcomes in both the general population 14,24,25 and patients with CKD. 15,26,27 Some retrospective and observational analyses as well as shortterm uncontrolled data suggested potential survival or cardiovascular benefit of 1,25(OH) 2 D 3 treatment in patients with CKD. [17][18][19]28,29 However, controlled data remain scarce.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] In CKD patients, lower vitamin D concentrations have been associated with an increased risk of mortality, 22,23 cardiovascular complications, 24 and renal disease progression. 25 These findings have resulted in a number of small-to mediumsized prospective randomized controlled trials (RCTs) with the use of active vitamin D analogs targeting reduction of (residual) proteinuria in CKD patients.…”
mentioning
confidence: 99%
“…Drechsler et al investigated the impact of vitamin D status on cardiovascular outcomes and fatal infections in haemodialysis patients and reported that severe vitamin D deficiency was strongly associated with sudden cardiac death, cardiac vascular event, and mortality, and there were borderline associations with stroke and fatal infection [10]. Findings from RCTs among patients free of advanced CKD have to be very cautiously extrapolated to haemodialysis patients.…”
Section: Heart Diseasementioning
confidence: 99%
“…Two more studies among African Americans also showed a high prevalence of vitamin D deficiency in patients with heart failure. Interestingly, not all heart failure patients with vitamin D deficiency show elevations in PTH levels, but those with secondary hyperparathyroidism have more severe forms of heart failure [10].…”
Section: Heart Diseasementioning
confidence: 99%